ANALISIS KEUNTUNGAN USAHA TANI CENGKEH (STUDI KASUS DESA SULUUN RAYA) - Heince A. A. Lolowang; Vicky V. J. Palenewen; Arie D. P. Mirah (Sam Ratulangi University, 2016)
This study aims to find out how much benefit the clove farmers got and how much Break Event Point (BEP) in volume and price of production were obtained by clove farmers. The research was conducted by colecting primary data through interviews using a structured simple questionnaire. Interviews were conducted in the Suluun Raya Village, Sub-district of Suluun Tareran. Total samples are 30 respondents. It has selected intentionally (purposive sampling). To achieve the research objectives, the indicator analysis used the analysis of production, cost, revenue and profit. Total production of cloves from 30 respondents in the Village of Suluun Raya was 33,020 kg with an average production of 1,100.6 kg, for a total cost of IDR 1,587,078,500, with an average of IDR 52,902,617, for a total revenue of IDR 3.22865 billion with an average of IDR 107,621,666.7, and for a total profit of IDR 1,699,232,967 with an average of IDR 54.71905 million. Clove businesses in the Village of Suluun Raya has given benefits to farmers where the value of average of Revenue- Cost Ratio obtained 1.80. Thus clove farm in the village of Suluun Raya was very profitable. The Break Event Point volume of production was reached when the production rate of 542.942 kg. Average production volume of clove farmers was 1101 Kg means that clove businesses profitable for farmers. The Break Event Point was reached when the price of production of IDR 48 050/kg. Average price of cloves of IDR 97 433/kg means that the price of cloves in the Village of Suluun Raya profitable for farmers.